2014
DOI: 10.3109/09593985.2014.902148
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy in the treatment of ankle hemophilic arthropathy. A randomized pilot study

Abstract: Both physiotherapy interventions improved the range of movement and lessened pain in patients with ankle arthropathy. No haemarthrosis was recorded during treatment or during the follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 26 publications
(31 reference statements)
4
55
0
Order By: Relevance
“…In a first phase, after discarding the 116 articles repeated among the various documentary sources, the titles and abstract of the remaining 67 studies were analyzed. Finally, following the selection process, only 10 articles [19][20][21][22][23][24][25][26][27][28] met the established criteria. Figure 1 shows the flow diagram with the selection made according to the criteria described above.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a first phase, after discarding the 116 articles repeated among the various documentary sources, the titles and abstract of the remaining 67 studies were analyzed. Finally, following the selection process, only 10 articles [19][20][21][22][23][24][25][26][27][28] met the established criteria. Figure 1 shows the flow diagram with the selection made according to the criteria described above.…”
Section: Search Resultsmentioning
confidence: 99%
“…On the other hand, the 3 articles that assessed post-follow-up [22,23,28] showed that none of the patients with hemophilia dropped out in this last assessment. The evaluation of the quantitative analysis of the selected studies is shown in Table 4.…”
Section: Methodological Variablesmentioning
confidence: 99%
See 3 more Smart Citations